2018
DOI: 10.1038/nature25436
|View full text |Cite
|
Sign up to set email alerts
|

A clumpy and anisotropic galaxy halo at redshift 1 from gravitational-arc tomography

Abstract: Every star-forming galaxy has a halo of metal-enriched gas that extends out to at least 100 kiloparsecs, as revealed by the absorption lines that this gas imprints on the spectra of background quasars. However, quasars are sparse and typically probe only one narrow beam of emission through the intervening galaxy. Close quasar pairs and gravitationally lensed quasars have been used to circumvent this inherently one-dimensional technique, but these objects are rare and the structure of the circumgalactic medium … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
77
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 44 publications
12
77
7
Order By: Relevance
“…It is well known that the O VI equivalent width is anticorrelated with the projected separation from the host galaxy (e.g., Tripp et al 2008;Wakker & Savage 2009;Chen & Mulchaey 2009;Prochaska et al 2011;Tumlinson et al 2011;Mathes et al 2014;Johnson et al 2015;Kacprzak et al 2015). This is similar to the anti-correlation observed between Mg II equivalent width and impact parameter (e.g., Bergeron & Boissé 1991;Steidel 1995;Bouché et al 2006;Kacprzak et al 2008;Chen et al 2010a;Bordoloi et al 2011;Nielsen et al 2013b;Kacprzak et al 2013;Lan et al 2014;Lan & Mo 2018;Lopez et al 2018;Rubin et al 2018). Both O VI and Mg II exhibits a bi-modal azimuthal angle distribution, suggesting a co-spatial behavior and possibly a kinematic con-nection or origin (Bouché et al 2012;Kacprzak et al 2012aKacprzak et al , 2015.…”
Section: Introductionsupporting
confidence: 80%
“…It is well known that the O VI equivalent width is anticorrelated with the projected separation from the host galaxy (e.g., Tripp et al 2008;Wakker & Savage 2009;Chen & Mulchaey 2009;Prochaska et al 2011;Tumlinson et al 2011;Mathes et al 2014;Johnson et al 2015;Kacprzak et al 2015). This is similar to the anti-correlation observed between Mg II equivalent width and impact parameter (e.g., Bergeron & Boissé 1991;Steidel 1995;Bouché et al 2006;Kacprzak et al 2008;Chen et al 2010a;Bordoloi et al 2011;Nielsen et al 2013b;Kacprzak et al 2013;Lan et al 2014;Lan & Mo 2018;Lopez et al 2018;Rubin et al 2018). Both O VI and Mg II exhibits a bi-modal azimuthal angle distribution, suggesting a co-spatial behavior and possibly a kinematic con-nection or origin (Bouché et al 2012;Kacprzak et al 2012aKacprzak et al , 2015.…”
Section: Introductionsupporting
confidence: 80%
“…We have studied the cool and enriched CGM of a z = 0.7 star-forming galaxy (G1) via the gravitational arctomography technique (Lopez et al 2018), i.e., using a bright giant gravitational arc as background source. G1 appears to be an isolated and sub-luminous disky galaxy, seen at an inclination angle i ≈ 45 • .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the paucity of the latter, lensed sources are able to resolve the CGM of intervening galaxies on kpc scales, albeit at a sparse sampling. More recently, Lopez et al (2018) have shown that the spatial sampling can be greatly enhanced by using giant gravitational arcs. Comparatively, these giant arcs are very extended (e.g., Sharon et al 2019) and thus can probe the gaseous halo of individual galaxies on scales of 1-100 kpc at a continuous sampling, nicely matching typical CGM scales.…”
Section: Introductionmentioning
confidence: 99%
“…One cannot 'image' individual systems (though some galaxies can be probed with multiple background sources, see e.g. Bechtold et al 1994;Dinshaw et al 1995;Hennawi et al 2006;Crighton et al 2010;Lopez et al 2018), meaning that radial trends must be inferred from samples of absorbers with diverse impact factors (e.g. Stocke et al 2013;Tumlinson et al 2013;Turner et al 2014;Borthakur et al 2015;Burchett et al 2016;Bielby et al 2019).…”
Section: Introductionmentioning
confidence: 99%